PEREGEE-SYZYGY TIDES IN ATMOSPHERE - Sidorenkov, N. S.; Wilson, Ian (Одеські астрономічні публікації, 2019)
It is shown that in 2016/17 the smoothed anomalies of air temperature in The European Territory of Russia repeated the course of the perigee distance, which varies along the sinusoid with a period of 206 days. Discovered the basic pattern perigee-syzygy tides: 206 daily beating pressure anomalies for the new moons and full moons. Pressure anomalies in the full moon and new moon can be approximated by sinusoids with periods of envelope beating about 412 days and opposite phases. The range of oscillations in the antinodes reaches 40 MB, which in order of magnitude is quite comparable to the real SYNOPTIC fluctuations in atmospheric pressure.